Early algebra in elementary schools: Trends, approaches, and challenges - Fitrianna, Aflich Yusnita; Rohim, Dhina Cahya (CV. Pustaka Literasi Ilmiah, 2025)
Early algebra constitutes an essential foundation in elementary education because it supports students’ relational reasoning, structural understanding, and generalization abilities from an early age. However, many studies indicate that algebra instruction in elementary schools remains dominated by procedural arithmetic approaches, which often lead to persistent conceptual difficulties and misconceptions, particularly during the transition to formal algebra. Therefore, this study aims to review and synthesize research on early algebra in elementary education to provide a systematic overview of research foci, instructional approaches, and existing limitations and research gaps. This study employed a literature review of articles retrieved from Google Scholar using the keywords early algebra, early algebra in elementary schools, and early algebra in primary education published between 2020 and 2025. A total of 49 articles were collected and screened based on relevance criteria, resulting in 39 articles for analysis. The research instrument was an article analysis sheet, and the data were analyzed using thematic analysis by classifying the articles into eight categories of study. The results show that early algebra research primarily focuses on identifying students’ difficulties and misconceptions, particularly related to variables, the meaning of the equal sign, and the arithmetic-to-algebra transition. Dominant instructional approaches include multiple representations, pattern- and relationship-based tasks, problem-based learning, and game-based learning. The findings also highlight the importance of teacher competence, curriculum coherence, and policy support in early algebra implementation. This study recommends strengthening concept-oriented instruction, enhancing teacher professional development, and conducting further research on the sustainability and scalability of early algebra implementation